Encyclopedia of private international law - Basedow, Jürgen, 1949-; Rühl, Giesela, 1974-; Ferrari, Franco, 1965-; Miguel Asensio, Pedro A. de (Edward Elgar Publishing, 2017)
The Encyclopedia of Private International Law quite simply represents the definitive reference work in the field. Bringing together 194 authors from 57 countries the Encyclopedia sheds light on the current state of Private International Law around the globe, providing unique insights into the discipline and how it is affected by globalization and increased regional integration. The role and character of Private International Law has changed tremendously over the past decades. With the steady increase of global and regional inter-connectedness the practical significance of the discipline has grown. And so has the number of legislative activities on the national, international and, most importantly, the European level. The Encyclopedia consists of four parts. The first two parts describe topical aspects of Private International Law in the form of 247 alphabetically sorted entries. The third part describes the Private International Law regimes of 80 countries in the form of national reports. The fourth part comprises a collection of national codifications and provisions of Private International Law in English translation.